Effect of Tube Voltage on the Use of Iterative Reconstruction on Computed Tomography Brain Examination - Muhammad Irsal; Nurbaiti Nurbaiti; Aulia Narendra Mukhtar; Shinta Gunawati; Wahyu Hidayat (Jurnal Teori dan Aplikasi Fisika, 2021)
Iterative reconstruction can optimize radiation dose and improve image quality on CT scan. This research method is quantitative analytic with the analysis of the results of the head CT examination parameters associated with image quality to changes in variations of 80 kV, 100 kV, 120 kV with the use of iterative reconstruction. Image quality measurements are the Hounsfield Unit (HU) value, standard deviation, and Signal to Noise Ratio (SNR) using Radiant Viewers. Effective dose measurement using the Dose Length Product (DLP). Then perform the Kruskal Wallis test to determine the difference in the SNR value to tube tension and Iterative Reconstruction using IBM SPSS version 24. The image quality results of the HU value increase due to changes in the kV value, but the value does not change significantly when the iDose changes, for standard deviation experiences decrease due to changes in kV, but the value of the value does not experience a significant change at the time of change in iDose, while SNR increases due to changes in kV value and changes in iDose. The percentage ratio of the effective dose in the use of standard kV with 80 kV decreased radiation dose by 62%, while at 100 kV there was a decrease of 25%, and the use of 120 kV experienced an increase of 25%. The results of the Kruskal Wallis test p-value <0.001, therefore it can be concluded that there is a difference in the SNR image quality at each change in iDose and kV parameters.